Career Orientation, Work-Life Balance, and Resilience on Leather Footwear MSME Performance - Yudi Wahyudin Suwandi; Imas Komariyah; Asep Ghofir Ali; Resty Ismawanti; Vidya Ramadhan Putra Pratama (AIBPM Publisher, 2026)
Micro, Small, and Medium Enterprises (MSMEs), particularly in the leather footwear sector, face competitive challenges that require strengthening human resources as a key factor of performance. This study aims to analyze the effects of career orientation, work-life balance, and resilience on MSME performance. The research employed a quantitative approach with a cross-sectional design through a survey of 153 MSME owners using a Likert-scale questionnaire. Data were analyzed using multiple linear regression supported by validity, reliability, and classical assumption tests. The results show that career orientation (b = 0.276, p 0.001), work-life balance (b = 0.183, p = 0.016), and resilience (b = 0.451, p 0.001) positively and significantly influence MSME performance, with resilience emerging as the strongest predictor. Furthermore, the model explains 61.1% of the variance in MSME performance (R² = 0.611). These findings indicate that psychological resources play an important role in improving MSME performance in a dynamic environment. This study extends the Resource-Based View (RBV) perspective by emphasizing the importance of intangible assets as a source of competitive advantage, particularly in the creative leather footwear industry.